Magnetic properties and microstructures of cobalt substituted barium hexaferrites derived from steel waste product via mechanical alloying technique - Azis, Raba'ah Syahidah; Hashim, Mansor; Zakaria, Azmi; Hassan, Jumiah; Daud, Noruzaman; Mohd Shahrani, Nuraine Mariana; Pua, Chong Siang (Trans Tech Publications, 2016)
The mechanical alloying technique was used to prepare barium hexaferrite (BaM) with 3, 5, 10 and 20 wt% cobalt oxide (Co3O4). In this work, steel waste flakes were cold-rolling steel mill for several hours to form a fine powder. The steel waste powder was purified by using magnetic separation to isolate the magnetic and non magnetic particles. The method was continued for Curie temperature separation technique to separate the magnetic ions by varied Curie temperature of the magnetic powder. The purified powder was then oxidize at 500 °C at 6 °C/mins to form hematite, Fe2O3. The steel waste-derived hematite was used as the raw material in preparing BaM ferrites. The BaCO3, Fe2O3and different percentages of Co3O4 (Co) were mixed and milled for several hours by using mechanical alloying. The powder were pelletised in 11 × 1 mm (diameter × height) and the sintered at 1200 °C for 10 hours. The addition of Co2+/3+ ions to the BaM shows a varying in the magnetic properties of BaM. By increasing the Co doping, the remanence Mr was reduced from 17.6 emu/g to 6.2 emu/g. The coercivity Hc results varying magnitude from 102 Oe to 1079 Oe. The Mr and Hc of undoped BaM is obtain at 14.6 emu/g and 860 Oe, respectively. The grain size of BaM also increases with Co doping. The densities of the compounds are decreasing with increasing Co doping with a maximum value of 4.2 g/cm3.